Polyphasic Characterization of the Biocontrol Potential of a Novel Strain of Trichoderma atroviride Isolated from Central Mexico - Karla Ivonne González-Martínez; Ma. Soledad Vázquez-Garcidueñas; Alfredo Herrera-Estrella; Sylvia P. Fernández-Pavía; Rafael Salgado-Garciglia; John Larsen; Salvador Ochoa-Ascencio; Gerardo Rodríguez-Alvarado; Gerardo Vázquez-Marrufo (Journal of Fungi)
This work describes the characterization of Trichoderma atroviride strain CMU-08, isolated from Michoacán, Mexico. CMU-08 demonstrated robust growth and conidiation across a temperature range from 16 to 32 °C and a pH range from 4 to 9 on potato dextrose agar (PDA) and malt extract agar (MEA) media. The strain is an efficient antagonist of six species of phytopathogenic fungi and oomycetes in PDA, MEA, and Vogel minimal medium (VMM). Antagonist mechanisms of CMU-08 included direct mycoparasitism observed in dual-culture assays, as well as antibiosis attributed to growth inhibition via both volatile and non-volatile metabolites, with the effectiveness varying depending on the test phytopathogen and culture medium. Extracellular filtrates (ECFs) recovered from liquid cultures of CMU-08 under basal and induced conditions using Botrytis cinerea cell walls significantly inhibited their growth at a concentration of 750 µg/mL. Moreover, in detached tomato leaf assays, these ECFs reduced foliar damage caused by B. cinerea by 24–34%. The volatile organic compounds (VOCs) produced by CMU-08 also exhibited substantial efficacy, reducing foliar damage by up to 50% in similar tests. Despite showing no basal extracellular chitinase enzymatic activity, CMU-08 demonstrated significant induction of this activity in cultures supplemented with B. cinerea and Fusarium sp. cell walls. Four genes encoding extracellular chitinases (chit33, chit36, ech42, and locus 217415) showed different dynamics of transcriptional regulation during the dual-culture confrontation of strain CMU-08 with B. cinerea and Fusarium sp., varying according to the phytopathogen and the interaction stage. The CMU-08 strain shows physiological versatility and employs a variety of antagonist mechanisms toward different species of phytopathogenic microorganisms, making it a good candidate for developing a biocontrol product for field application.